2021
DOI: 10.1007/s10147-021-01997-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia in advanced and metastatic soft tissue sarcoma

Abstract: Introduction Advanced or metastatic soft tissue sarcoma (a/mSTS) is associated with a dismal prognosis. Patient counseling on treatment aggressiveness is pivotal to avoid over- or undertreatment. Recently, evaluation of body composition markers like the skeletal muscle index (SMI) became focus of interest in a variety of cancers. This study focuses on the prognostic impact of SMI in a/mSTS, retrospectively. Methods 181 a/mSTS patients were identified, 89 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Many reports have shown that sarcopenia is closely related to the prognosis of patients with various malignant tumors. 3,[6][7][8][9][10][11]13,[19][20][21] However, different pathological types of sarcomas are not identical in treatment and prognosis, so we conducted a study on the exact pathological type of sarcomas and drew relevant conclusions. Meanwhile, the effect of sarcopenia on the post-surgical outcomes of patients with liposarcoma undergoing en bloc compartment resection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have shown that sarcopenia is closely related to the prognosis of patients with various malignant tumors. 3,[6][7][8][9][10][11]13,[19][20][21] However, different pathological types of sarcomas are not identical in treatment and prognosis, so we conducted a study on the exact pathological type of sarcomas and drew relevant conclusions. Meanwhile, the effect of sarcopenia on the post-surgical outcomes of patients with liposarcoma undergoing en bloc compartment resection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 The advanced studies showed that sarcopenia is associated with prognostic parameters in advanced or metastatic STS and rst-line therapy response. 13 Therefore, body composition parameters should be deeply investigated to evaluate the next step of treatment, which needs forward prognostication systems to avoid over-or undertreatment as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that sarcopenia is closely related to the prognosis of patients with various malignant tumors. [ 3 , 6 11 , 13 , 19 21 ] However, different pathological types of sarcomas are not identical in treatment and prognosis, so we conducted a study on the exact pathological type of sarcomas and drew relevant conclusions. Meanwhile, the effect of sarcopenia on the post-surgical outcomes of patients with liposarcoma undergoing en bloc compartment resection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, sarcopenia is linked to the prognostic state of some pathologies, e.g., in those that affect the intestinal function and, as aforementioned, the absorption of nutrients as reported in abdominal hernias [13] and inflammatory bowel disease (IBD) [14]. Furthermore, sarcopenia has been recently related to the prognosis of various tumors [15][16][17][18], which leads to a monitoring status at the initial stage, as well as during and after chemotherapy. This narrative review aims to summarize the key molecular mechanisms of sarcopenia, the recent and future directions of the microRNAs for diagnosis and prognosis, and several strategies with an emphasis on nutrition to counteract the progression of this condition.…”
Section: Introductionmentioning
confidence: 99%